Enterococcus durans Cardiac Implantable Electronic Device Lead Infection and Review of Enterococcus durans Endocarditis Cases - Milan Radovanovic; Djordje Jevtic; Michel K. Barsoum; Janki Patel; Igor Dumic (Medicina, 2022)
Introduction: Cardiac implantable electronic device (CIED) infections present a growing problem in medicine due to a significant increase in the number of implanted devices and the age of the recipient population. Enterococcus spp. are Gram-positive, facultative anaerobic, lactic acid bacteria; they are relatively common pathogens in humans, but uncommon as the cause of CIED lead infections. Only eight cases of Enterococcus durans endocarditis have been reported in the literature thus far; however, there are no reported cases of Enterococcus durans CIED lead infection. Case presentation: A 58-year-old gentleman with a previously implanted St. Jude Medical single-chamber implantable cardioverter–defibrillator (ICD) due to tachy/brady arrhythmias presented with nonspecific constitutional symptoms (i.e., low-grade fevers, chills, fatigue), and was found to have innumerable bilateral pulmonary nodules via computed tomography angiography of the chest. Many of these pulmonary nodules were cavitated and highly concerning for septic pulmonary emboli and infarcts. Within 24 h from presentation, blood cultures in all four culture bottles grew ampicillin- and vancomycin-susceptible Enterococcus durans. Transthoracic echocardiogram confirmed vegetations on the ICD lead in the right ventricle. The patient underwent laser extraction of the ICD lead with generator removal and recovered completely after a 6-week intravenous antibiotic course. Conclusion: To our knowledge, this is the first report of CIED lead infection caused by Enterococcus durans. In this case, management with antibiotics along with ICD lead extraction led to complete recovery. Clinicians should be aware of this rare but potentially devastating infection in patients with native and artificial valves, but also in those with CIEDs.